Peran Bawaslu dalam Penanganan Sengketa Pilkada Tahun 2024 di Kabupaten Serang - Muhamad Rayhan Ferdiansyah Putra; Mohamad Ikrom Arasid; Malik Fatoni (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to analyze the role of the Election Supervisory Board (BAWASLU) in the implementation of the 2024 Regional Head Election (Pilkada) in Serang Regency, with a particular focus on the mechanisms for resolving electoral disputes during the election process. It also seeks to identify the types of electoral disputes and evaluate the effectiveness of BAWASLU in carrying out its supervisory and quasi-judicial functions at the local level. This research adopts a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews with key stakeholders, direct field observations, and documentation analysis of official reports and BAWASLU decisions. The data were analyzed using the Miles and Huberman interactive model, involving data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation and member checks. The findings reveal that BAWASLU Serang Regency plays a strategic role in safeguarding the integrity of the regional elections, yet it still faces challenges such as limited human resources, weak adjudication authority, and local political pressure. The disputes that occurred, including the case of the Repeat Voting (PSU), underscore the need for institutional reform. In conclusion, BAWASLU's role is crucial in electoral supervision and dispute resolution, but it requires strengthening in terms of regulations, institutional capacity, and public participation to ensure fair, democratic, and credible elections.